Regulation of type II transmembrane serine proteinase TMPRSS6 by hypoxia-inducible factors: new link between hypoxia signaling and iron homeostasis. - Lakhal, S; Schödel, J; Townsend, A; Pugh, C; Ratcliffe, P; Mole, D (2011)
Hepcidin is a liver-derived hormone with a key role in iron homeostasis. In addition to iron, it is regulated by inflammation and hypoxia, although mechanisms of hypoxic regulation remain unclear. In hepatocytes, hepcidin is induced by bone morphogenetic proteins (BMPs) through a receptor complex requiring hemojuvelin (HJV) as a co-receptor. Type II transmembrane serine proteinase (TMPRSS6) antagonizes hepcidin induction by BMPs by cleaving HJV from the cell membrane. Inactivating mutations in TMPRSS6 lead to elevated hepcidin levels and consequent iron deficiency anemia. Here we demonstrate that TMPRSS6 is up-regulated in hepatic cell lines by hypoxia and by other activators of hypoxia-inducible factor (HIF). We show that TMPRSS6 expression is regulated by both HIF-1α and HIF-2α. This HIF-dependent up-regulation of TMPRSS6 increases membrane HJV shedding and decreases hepcidin promoter responsiveness to BMP signaling in hepatocytes. Our results reveal a potential role for TMPRSS6 in hepcidin regulation by hypoxia and provide a new molecular link between oxygen sensing and iron homeostasis.